Answer to Question #120339 in Philosophy for nina

Question #120339
By using only basic rules of QL and SL, prove the following:
a. ∃x¬Px ∴ ¬∀xPx
b. ∅ ∴ ∀x¬Px → ¬∃xPx
c. ∃x (Px & ∀y (Py → y=x)) ∴ ∀x∀y ((Px & Py) → x=y)
d. ∃x (Fx & ∀y (Fy → x=y)) ∴ ∃xFx & ∀x∀y((Fx & Fy) → y=x)
1
Expert's answer
2020-06-05T12:08:09-0400
Dear nina, your question requires a lot of work, which neither of our experts is ready to perform for free. We advise you to convert it to a fully qualified order and we will try to help you. Please click the link below to proceed: Submit order

Need a fast expert's response?

Submit order

and get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

Comments

No comments. Be first!

Leave a comment

Ask Your question

LATEST TUTORIALS
New on Blog
APPROVED BY CLIENTS